A rightward shift in the visuospatial attention vector with healthy aging - Christopher S.Y. Benwell; Gregor eThut; Ashley eGrant; Monika eHarvey (Frontiers in Aging Neuroscience, 2014)
The study of lateralised visuospatial attention bias in non-clinical samples has revealed a systematic group-level leftward bias (pseudoneglect), possibly as a consequence of right hemisphere dominance for visuospatial attention. Pseudoneglect appears to be modulated by age, with a reduced or even reversed bias typically present in elderly participants. It has been suggested that this shift in bias may arise due to disproportionate aging of the right hemisphere and/or an increase in complementary functional recruitment of the left hemisphere for visuospatial processing. In this study, we report rightward shifts in subjective midpoint judgement relative to healthy young participants whilst elderly participants performed a computerized version of the landmark task (in which they had to judge whether a transection mark appeared closer to the right or left end of a line) on three different line lengths. This manipulation of stimulus properties led to a similar behavioural pattern in both the young and the elderly: a rightward shift in subjective midpoint with decreasing line length, which even resulted in a systematic rightward bias in elderly participants for the shortest line length (1.98° of visual angle). Overall performance precision for the task was lower in the elderly participants regardless of line length, suggesting reduced landmark task discrimination sensitivity with healthy aging. This rightward shift in the attentional vector with healthy aging is likely to result from a reduction in right hemisphere resources/dominance for attentional processing in elderly participants. The significant rightward bias in the elderly for short lines may even suggest a reversal of hemisphere dominance in favour of the left hemisphere/right visual field under specific conditions.